ABIOTIC ECOLOGICAL CHARACTERISTICS OF THREE SELECTED FISH FARMS IN BABYLON AND BASRAH PROVINCES, IRAQ. - Hussein, S. A.; Abed, J. M.; Salem, N. K. (Iraqi Journal of Aquaculture, 2022)
The study is part of a comprehensive work to investigate impact of fish enemies on cultivated species. It has taken in consideration some vital abiotic characteristics necessary for cultivated fishes. Three fish farms were selected in two provinces, namely Al-Manahel fish farm (presently called Al-Belad) in Babylon province; Basrah University fish farm (Marine Science Center) and Al-Mutawaa fish farm situated south to city of Basrah. Water samples were monitored on monthly basis for the period from January to October 2002. Several parameters namely, temperature, pH, salinity, total alkalinity and total hardness were measured. The highest water temperature (31ºC) was recorded in July and August from Al-Mutawaa fish farm and the maximum pH value 8.0 was encountered during January from Basrah university fish farm and the lowest pH= 7.2 in May from the same farm. Results indicate a notable rise in salinity in Al-Mutawaa fish farm and the highest (6.0 g/L) encountered in June and the lowest (2.8 g/L) in March. The maximum concentration of total alkalinity (172 mg/L) was from Al-Mutawaa as well recorded in September. Values of total hardness were almost similar in Al- Manahel and Basrah university fish farms, but the latter revealed a bit higher value in May (581 mg/L), whereas Al-Mutawaa fish farm showed, by no means, the highest concentrations all the year round, but the maximum (880 mg/L) was detected in March.